Degradable composite hyaluronic acid polymer hemostatic material and application thereof
By preparing composite polymer hemostasis material (HA-ADP) of hyaluronic acid and adenosine diphosphate, the problem of insufficient effect of existing hemostasis materials in high pressure bleeding is solved, and efficient control of deep tissue bleeding is achieved. Good biocompatibility and complete degradation performance.
Patent Information
- Application Number
- CN202411726290.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-14
AI Technical Summary
Existing degradable hemostasis materials are not effective in high pressure bleeding, and they have the risk of immunogenicity and viral transmission, making it difficult to effectively control deep tissue bleeding.
Hyaluronic acid and adenosine diphosphate were used as raw materials to prepare composite hyaluronic acid polymer hemostasis material (HA-ADP) through amidation reaction. This material achieves efficient hemostasis by activating platelets and accelerating coagulation pathways.
It has achieved efficient control of deep tissue hemorrhage, has good biocompatibility and complete degradation performance, and is suitable for bleeding of mild and moderate organ injury.
Smart Images

Figure CN119424719A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical materials, and specifically relates to a degradable composite hyaluronic acid polymer hemostatic material and application thereof. Background Art
[0002] Degradable hemostatic materials play a vital role in the field of surgical operations and trauma care. They are usually made of natural or synthetic biocompatible polymers, such as fibrinogen, collagen, gelatin, cellulose and starch. They cause less adverse reactions in the body and reduce the risk of immune rejection of implanted materials in patients. Since degradable hemostatic materials can be gradually decomposed and absorbed in the body, secondary surgery can be avoided. In the early 20th century, it was reported that fibrinogen had excellent hemostatic ability, but it comes from animal or human blood, so fibrinogen and thrombin products have the risk of immunogenicity and virus transmission. Like fibrinogen, collagen and gelatin from animals also have the risk of immunogenicity. In order to reduce immunogenicity and infectiousness, the main component of microporous hemostatic balls Arista is starch. Due to its in vivo degradation characteristics, it can be directly used for bleeding from small wounds in organ surgery, but it only relies on the physical properties of self-swelling after absorbing water, and the effect is poor for bleeding with higher pressure. In order to be able to effectively control bleeding, these materials can have or enhance hemostatic function through chemical modification or structural design, making them an ideal substitute for traditional non-degradable hemostatic materials. Summary of the invention
[0003] The technical problem to be solved by the present invention is to prepare a completely degradable and efficient hemostatic material.
[0004] The technical solution of the present invention is as follows: The invention provides a degradable composite hyaluronic acid polymer hemostatic material, which is prepared by taking hyaluronic acid and adenosine diphosphate as raw materials, adding a condensing agent and an activating agent to undergo an amidation reaction.
[0005] Wherein, the molar ratio of the hyaluronic acid, adenosine diphosphate, condensing agent and activating agent is (1-3):1:1:1.
[0006] Preferably, the molar ratio of the hyaluronic acid, adenosine diphosphate, condensing agent and activating agent is 1:1:1:1.
[0007] Furthermore, the condensing agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and the activating agent is 1-hydroxybenzotriazole.
[0008] The present invention also provides a method for preparing the degradable composite hyaluronic acid polymer hemostatic material, comprising the following steps: Dissolve hyaluronic acid in deionized water, add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole, dissolve, add adenosine diphosphate, purify after the reaction, and obtain the hemostatic material HA-ADP, which is dried and stored, wherein the molar ratio of the hyaluronic acid, adenosine diphosphate, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole is (1-3):1:1:1.
[0009] Preferably, the molar ratio of the hyaluronic acid, adenosine diphosphate, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole is 1:1:1:1.
[0010] Furthermore, when hyaluronic acid is dissolved in deionized water, the ratio of hyaluronic acid to deionized water is: 100-150 mL of deionized water per 1 g of hyaluronic acid.
[0011] Preferably, the ratio of the hyaluronic acid to deionized water is: 100 mL of deionized water per 1 g of hyaluronic acid.
[0012] Furthermore, the reaction is carried out under stirring, and the reaction time is: at least 24 hours.
[0013] Furthermore, the purification is performed by dialysis, the molecular weight cutoff of the dialysis is 3500 Da, the dialysis time is 96 hours, the dialysis fluid of the dialysis is deionized water, and the deionized water is replaced every 12 hours.
[0014] Furthermore, the drying is carried out by freeze-drying.
[0015] The present invention also provides a method for preparing the degradable composite hyaluronic acid polymer hemostatic material, comprising the following steps: Adenosine diphosphate was dissolved in dichloromethane to obtain an adenosine diphosphate solution, triethylamine was dissolved in dichloromethane to obtain a triethylamine solution, hyaluronic acid was dissolved in thionyl chloride and stirred under reflux to form a hyaluronic acid solution, which was then dissolved in dichloromethane after rotary evaporation for later use, adenosine diphosphate solution and triethylamine solution were added, and the mixture was stirred to obtain HA-ADP particles.
[0016] Furthermore, the concentration of the adenosine diphosphate solution is 1M.
[0017] Preferably, the ratio of adenosine diphosphate to dichloromethane is: 1 mL of dichloromethane for every 0.43 g of adenosine diphosphate.
[0018] Furthermore, the concentration of the triethylamine solution is 1.5M.
[0019] Preferably, the ratio of triethylamine to dichloromethane is: 30 mL of dichloromethane for every 4.55 g of triethylamine.
[0020] Furthermore, the concentration of the hyaluronic acid solution is 1M.
[0021] Preferably, the ratio of hyaluronic acid to thionyl chloride is: 2 mL of thionyl chloride for every 0.76 g of hyaluronic acid.
[0022] Furthermore, the stirring and refluxing conditions are: time is 4 hours, temperature is 120°C.
[0023] Furthermore, the rotary evaporation temperature is 50°C.
[0024] Furthermore, the method of adding is dropwise addition.
[0025] Furthermore, the stirring conditions are: time is 24 hours, temperature is 20-30°C.
[0026] The present invention also provides a degradable composite hyaluronic acid polymer hemostatic material prepared by the preparation method.
[0027] The present invention also provides application of the degradable composite hyaluronic acid polymer hemostatic material in preparing medical hemostatic products.
[0028] Beneficial effects of the present invention: The present invention aims at the difficulties in treating deep tissue bleeding, and provides a composite hyaluronic acid polymer hemostatic material (HA-ADP) that is completely degradable, has multiple coagulation mechanisms, good biocompatibility, high hemostatic activity, and can be used for hemostasis of deep tissue wounds. The present invention cross-links ADP and HA through structural design and chemical modification, and the composite HA-ADP is freeze-dried into a sponge-like state and used as a wound healing promoting material. Secondly, the present invention also completes the optimization of the synthesis process of the hemostatic material, the research and optimization of the physicochemical properties, biological activity and hemostatic efficacy, and screens out the HA-ADP with the best performance through in vitro biocompatibility and hemostatic activity. It shows good hemostatic activity, hemostatic safety and complete degradation performance in vivo in the in vivo liver bleeding model. It can achieve hemostasis by activating platelets, accelerating the coagulation pathway with electronegativity, and accelerating the formation and cross-linking of fibrin, and is suitable for bleeding caused by mild to moderate organ damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 In vitro hemolysis diagram of ADP; Note: The horizontal axis represents different contents of ADP; the vertical axis represents the hemolysis rate of ADP.
[0030] Figure 2 ADP in vitro platelet activation diagram; Note: The horizontal axis represents different levels of ADP, and the vertical axis represents the percentage of platelet activation indicator CD 62P.
[0031] Figure 3 Infrared spectrum of HA-ADP (1:1); Note: the horizontal axis represents wavelength and the vertical axis represents transmittance.
[0032] Figure 4 NMR of different sample groups 1 H spectrum.
[0033] Figure 5 Scanning electron micrographs of HA-ADP (1:1), (a) × 50, (b) × 200, (c) × 500.
[0034] Figure 6 31 P element standard curve; Note: The horizontal axis represents the concentration of P element, and the vertical axis represents the CPS value.
[0035] Figure 7 Zeta potential diagram of HA-ADP with different ratios at different pH values; Note: The vertical axis represents the potential value.
[0036] Figure 8 In vitro coagulation time of HA-ADP; (a) a sample in vitro coagulation time diagram, wherein the ordinate represents the in vitro coagulation time of the sample, (b) a sample in vitro coagulation state diagram; wherein, # Representatives compared with Yunnan Baiyao group: ### p<0.005; * represents comparison with the blank group: ***p<0.005.
[0037] Fig. 9 In vitro coagulation index of HA-ADP; Note: The vertical axis represents the in vitro coagulation index.
[0038] Fig.10 Graphs of exogenous coagulation time (PT) and intrinsic coagulation time (APTT) of HA-ADP, where the ordinate represents coagulation time, ***p<0.001.
[0039] Fig.11 Platelet activation diagram of HA-ADP, where the ordinate represents the percentage of platelet activation indicator CD 62P, # Compared with the blank group: ### p<0.001; * represents comparison with ADP group: **p<0.01.
[0040] Fig.12 Effect diagram of different ratios of HA-ADP and FXII factor, (a) standard curve diagram, where the horizontal axis represents the content of FXII and the vertical axis represents the absorbance value of FXII at 450 nm; (b) FXII factor activation amount diagram, where the vertical axis represents the content of FXII.
[0041] Fig.13 In vitro hemolysis diagram of different HA-ADP ratio groups, (a) is the sample hemolysis data diagram, the ordinate represents the hemolysis rate, and (b) is the sample hemolysis diagram.
[0042] Fig.14 In vitro L929 cell toxicity of HA-ADP; Note: The vertical axis represents cell activity.
[0043] Fig.15 HA-ADP staining of L929 cells for viability.
[0044] Fig.16 Systemic acute toxicity diagram of Kunming mice in the HA-ADP (1:1) group; Note: The horizontal axis represents time, and the vertical axis represents body weight.
[0045] Fig.17 Diagram of the mouse liver injury and bleeding model.
[0046] Fig.18 Hemostatic efficacy based on the mouse liver injury bleeding model, where (a) shows the amount of blood loss in different groups of mice; (b) shows the hemostasis time in different groups of mice; (c) is a schematic diagram of partial blood loss in the HA-ADP (1:1) group of mice; (d) is a schematic diagram of partial blood loss in the blank group of mice.
[0047] Fig.19 Postoperative safety and in vivo degradation of mice in the HA-ADP (1:1) group, where (a) is the in vivo degradation graph of mice on days 2 and 5; (b) is the graph of weight changes of mice after surgery, with the horizontal axis representing time and the vertical axis representing weight; (c) is the histological analysis of the liver of mice after hemostasis (magnification, × 20). DETAILED DESCRIPTION
[0048] Degradable hemostatic materials play a vital role in the field of surgical operations and trauma care. They are usually made of natural or synthetic biocompatible polymers, such as fibrinogen, collagen, gelatin, cellulose and starch, and cause fewer adverse reactions in the body, reducing the risk of immune rejection of implanted materials in patients. Since degradable hemostatic materials can be gradually decomposed and absorbed in the body, secondary surgery can be avoided. These materials can not only effectively control bleeding, but also, through chemical modification or structural design, can simultaneously possess or enhance hemostatic function, making them an ideal alternative to traditional non-degradable hemostatic materials.
[0049] As one of the main components of the extracellular matrix, hyaluronic acid (HA) can be used as a tissue lubricant to maintain the extracellular space and regulate osmotic pressure. It has good biocompatibility, anti-inflammatory and wound healing effects, and can be used as a drug carrier to achieve targeted drug delivery to improve the bioavailability of drugs. Adenosine diphosphate (ADP), as one of the key molecules for intracellular signal transduction, can be used by the cell body and converted into energy substances; ADP is also related to platelet function. After vascular injury, ADP is released from the high-density platelet granules and triggers the shape change and activation of platelets by binding to its receptors.
[0050] The present invention is further described in detail below by way of examples, but the present invention is not limited in any way.
[0051] The experimental drugs and reagents used in the following examples are shown in Table 1.
[0052] Table 1 Main drugs and reagents The experimental instruments used in the following examples are shown in Table 2.
[0053] Table 2 Main experimental instruments The experimental animals used in the following examples are: Sprague Dawley (SD) rats, weight 180 ~ 220 g, male; New Zealand rabbits, weight, male 2 ~ 3 kg; Balb / c mice, weight 18 ~ 20 g, male; KM mice, weight 18 ~ 20 g, male; purchased from Beijing Keyu Animal Breeding Center, license number: SCXK (Beijing) 2018-0010. The experiment was approved by the Military Medical Research Institute (IACUC-DWZX-2020-503).
[0054] The data analysis method used in the following examples is: All statistical data were analyzed using GraphPad Prism and Origin software. Quantitative data are presented as mean ± SD of at least three tests. Significant differences were evaluated using one-way ANOVA, and differences were considered statistically significant when p values were less than 0.05.
[0055] Example 1 Preparation of a completely degradable hyaluronic acid composite material (HA-ADP) 1. In vitro hemolysis test The blood compatibility of adenosine diphosphate (ADP) was evaluated using rat whole blood. Fresh rat whole blood was mixed with 3.8% sodium citrate at a ratio of 9:1 (v / v), and fresh anticoagulated whole blood was diluted with normal saline at a ratio of 1:1 (v / v) for later use. Weigh 0.5 mg, 1 mg, 2 mg, 5 mg, and 10 mg of ADP samples and place them in 10 mL centrifuge tubes. 200 μL of diluted anticoagulated whole blood and 5 mL of normal saline were added and mixed. The normal saline group was used as a negative control, and the deionized water group was used as a positive control. Three parallel tubes were set up for each group. All centrifuge tubes were incubated at 37 °C for 1 h, centrifuged at 3000 r / min for 5 min, and the supernatant was aspirated. At the same time, the absorbance was measured at 545 nm using a UV-visible spectrophotometer. The hemolysis rate was calculated according to the following formula: The blood compatibility results of different doses of ADP determined by in vitro hemolysis method are as follows Figure 1 As shown in the figure, the hemolysis rate of 1 mg ADP is 4.69%. As the dose increases, ADP is hemolytic. The hemolysis rate of the negative control (normal saline) group is identified as 0%, and the hemolysis rate of the positive control (deionized water) group is identified as 100%. Compared with the distilled water group, when the ADP dose is lower than 1 mg, its hemolysis rate is less than 5%. As the dose increases, it gradually causes hemolytic reaction. The results show that ADP within the range of 1 mg has no obvious damage to red blood cells and has good blood compatibility.
[0056] 2. Platelet activation experiment Accurately weigh 10 mg of ADP and dilute ADP to 0.25 mg / mL, 0.5 mg / mL, and 1 mg / mL using PBS as solvent and diluent. For each concentration, take 1 mL of ADP and 200 μL of PRP (10 8 / mL) and incubate at 37 °C for 10 min. Centrifuge at 1200 × g for 10 min and discard the supernatant. Add 200 μL PBS and blow repeatedly to form a platelet suspension. Platelets without sample treatment were used as blank controls. APC-CD62P and PE-CD61 were added and mixed thoroughly. The mixture was incubated at 4 °C in the dark for 20 min. Add 1 mL Cell Staining Buffer to wash the unbound antibodies, centrifuge at 350 × g for 5 min and discard the supernatant. Repeat the washing 2 to 3 times, then add 0.5 mL Cell Staining Buffer and mix well before testing by flow cytometer.
[0057] By labeling resting and activated platelets with PE-CD61, platelets that can be activated by APC-CD62P are screened out, thereby obtaining the proportion of platelets activated by ADP. Figure 2 As shown, the results of flow cytometry experiments showed that compared with the blank group, 1 mg / mL ADP salt solution could significantly activate platelets, proving that ADP has the ability to activate platelets within a safe dose (1 mg) of blood compatibility.
[0058] 3. Preparation of fully degradable hyaluronic acid composite material (HA-ADP) Organic phase synthesis method: 0.43 g adenosine diphosphate (ADP) was dissolved in 1 mL dichloromethane (DCM) to obtain a 1 M solution, and 4.55 g triethylamine (Et3N) was dissolved in 30 mL DCM to obtain a 1.5 M solution. 0.76 g hyaluronic acid (HA) was dissolved in 2 mL thionyl chloride (SOCl2) and stirred at reflux for 4 h (120 °C) to form a 1 M solution, which was then dissolved in DCM after rotary evaporation (50 °C) for later use. 1 mM ADP and 1.5 mM Et3N were added dropwise, and HA-ADP particles of different sizes were obtained after stirring at room temperature for 24 h.
[0059] Aqueous phase synthesis method: 1 g of hyaluronic acid (HA) was dissolved in 100-150 mL of deionized water (DW) (preferably, 100 mL of deionized water was used for every 1 g of hyaluronic acid). Using the amount of HA added as a control, 1:1 (mol / mol) of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDCI) and 1-hydroxybenzotriazole (HOBt) were added and stirred vigorously for 20 min, and 1:1, 2:1, and 3:1 (mol / mol) of adenosine diphosphate (ADP) were added and stirred for at least 24 h. After the reaction was completed, the solution was purified by dialysis (cutoff 3500 Da) with DW (DW served as the dialysis fluid and was changed every 12 hours) for 96 h. The prepared fully degradable hemostatic materials (HA-ADP) with different ratios were freeze-dried and stored for further use. (Subsequent physical and chemical tests, in vitro and in vivo hemostatic activity studies, etc. are all samples of the aqueous phase synthesis method) The organic phase synthesis method and the aqueous phase synthesis method were used to prepare the fully degradable hyaluronic acid composite material (HA-ADP). The organic phase synthesis method served as a control for the aqueous phase synthesis method. Compared with the two, in the later synthesis, the product of the organic phase synthesis method needs to be dried first, then dissolved, dialyzed, and then freeze-dried, while the product of the aqueous phase synthesis can be directly dialyzed and then freeze-dried.
[0060] 4. Fourier transform infrared spectroscopy The HA-ADP sample was tested by a Nicolet IS5 infrared spectrometer from Nicolet, USA. The potassium bromide tablet method was used. The powder was evenly mixed and ground with KBr at a ratio of 1:100. The number of scans was 32 and the test wavelength range was 4000 ~ 500 cm -1 .
[0061] In order to clarify the characteristic groups of HA-ADP, the infrared spectrum of HA-ADP (1:1) is shown in Figure 3 As shown. FTIR spectrum of HA 1040 cm -1 The characteristic band of COC stretching vibration, 1744 cm -1 The characteristic band of -CO stretching vibration, 2913 cm -1 It is the characteristic band of -CH2 asymmetric stretching vibration. From the FTIR spectrum of ADP, we can see that 1245 cm -1 It is the characteristic band of the symmetric stretching vibration of the phosphate group P=O, 880 cm -1 It is the characteristic band of asymmetric stretching of phosphate group P=O. When ADP is grafted with HA, the characteristic peaks of HA and ADP appear in the FTIR spectrum of HA-ADP. In addition, 1561 cm -1 The characteristic bands of secondary amide complexes appeared, confirming the successful synthesis of HA-ADP.
[0062] 5. Nuclear Magnetic Resonance 1 H Spectrum 1 H spectra were measured using a Bruker 600M NMR spectrometer. Three different ratios of HA-ADP were completely dissolved in deuterium oxide and transferred to the original sample tube. The spectra were captured at room temperature, automatically corrected, and saved as 1 H spectral analysis.
[0063] Nuclear Magnetic Resonance 1 H spectrum results further confirmed the structure of HA-ADP. 1 The H-NMR results are as follows Figure 4 As shown in the figure, 1.9 ppm is the characteristic peak of the methyl group in HA, and 4.7 ppm is the characteristic peak of the sugar end group. 1 It can be seen from the H-NMR graph that 8.33 ppm and 8.56 ppm are the characteristic peaks of the carbon-nitrogen double bond groups in ADP. 1 The characteristic peaks of HA and ADP appeared in the H-NMR graph. In addition, the characteristic peak of the amide group appeared at 2.79 ppm, further confirming the successful synthesis of HA-ADP.
[0064] Example 2 Study on the physical and chemical properties of the fully degradable hyaluronic acid composite material (HA-ADP) 1. Scanning electron microscope Since the material itself is not conductive, a small amount of sample was taken for gold spraying and the sample microstructure was analyzed using a Hitachi Regulus 8230 electron microscope.
[0065] Scanning electron microscopy results showed the pore structure and surface morphology of HA-ADP, such as Figure 5 As shown, under different magnification conditions, it can be observed that HA-ADP has a three-dimensional network structure and a porous structure with a pore size of about 100 μm. The three-dimensional network porous structure can better absorb tissue fluid and blood during the hemostasis process, achieve the purpose of concentrating blood, and accelerate the hemostasis process.
[0066] 2. Determination of grafting rate After the HA-ADP sample was dialyzed and purified, the free ADP content was determined to be negligible. The grafting rate C of ADP in three different proportions of HA-ADP was determined by measuring the content of P element introduced into ADP. 31 The stock solution of P element standard solution was prepared into a solution with a concentration of 1000 ng / mL using 2% nitric acid solution as the diluent, and then diluted step by step into standard solution samples of 1, 5, 10, 50, 200, and 1000 ng / mL. The standard concentration of the element to be measured was used as the abscissa, and the ratio of the peak area of the element to be measured to the corresponding internal standard element was used as the ordinate to obtain the standard curve and linear regression equation.
[0067] Weigh 50 mg of HA-ADP in three different proportions accurately, dissolve in 2 mL of 70% nitric acid solution, and digest in a 98 °C water bath for 1 h. When the sample is digested to a clear solution without solids, place it in a fume hood and cool to room temperature. Use deionized water as the diluent and make up to 11 mL. Dilute the nitrated sample 400 times for ICP-MS detection 31 The P element content is B, and the theoretical value of the phosphorus element (the amount of ADP added) content is recorded as A. The calculation formula for the grafting rate C is as follows: Established and optimized ICP-MS instrument detection 31 The conditions of P element content are shown in Table 3.
[0068] Table 3 ICP-MS instrument parameters The grafting rate of ADP on the HA polymer chain was indirectly calculated by measuring the content of P element introduced by HA-ADP. The standard curve is shown in Figure 6, the P element standard curve established is as follows: 31 P element is in the range of 1 ~ 1000 ng / mL, R 2 = 1.00, indicating a good linear relationship, which can be used for the quantitative analysis of P element in HA-ADP. The content of P element in three different ratios of HA-ADP is shown in Table 4. Every 0.05 g of HA-ADP (1:1) contains (0.72 ± 0.02) mg of P element. According to the formula, the grafting rate of HA-ADP (1:1) is the highest (18.82%); while HA-ADP (3:1) has the lowest grafting rate (6.77%).
[0069] Table 4 Grafting rate of HA-ADP with different ratios 3. Zeta potential of different ratios of HA-ADP The samples were placed in deionized water using a Zetasizer Nano ZS90 nanoparticle size tester from Malvern, UK. The Zeta potential of the samples at different pH values (4, 5, and 6) was measured, with each sample measured three times.
[0070] The Zeta potential value can reflect the charge of dispersed particles. There are many -COO groups on the surface of HA-ADP that are not grafted with ADP and are beneficial to hemostasis. - The negative charge of the carboxyl group can activate the coagulation factor XII to XIIa of the intrinsic coagulation pathway, thereby triggering the intrinsic coagulation pathway of hemostasis and shortening the hemostasis time. Figure 7 It can be seen that in different acidic environments, the surfaces of HA and HA-ADP carry different amounts of negative charge. Compared with HA-ADP in other ratios, HA-ADP (3:1) carries the most negative charge. This is because the amount of HA grafted with ADP is the lowest, the exposed carboxylic acid groups are the most, and there are more free negative charges in the aqueous solution. As the pH increases, the negative charge of the sample gradually increases, indicating that the acidic environment inhibits the dissociation of the carboxylic acid groups in HA-ADP, and thus its hemostatic effect may be inhibited, but the negative charge on its surface can still promote the activation of the endogenous coagulation pathway.
[0071] Example 3 Study on the in vitro hemostatic properties and mechanism of a fully degradable hyaluronic acid composite material (HA-ADP) 1. In vitro coagulation time determination Accurately weigh 20 mg of the test sample (HA-ADP and Yunnan Baiyao powder, HA and ADP are converted according to the maximum content of HA-ADP) and place it in a 5 mL centrifuge tube. The blank centrifuge tube is a negative control, and Yunnan Baiyao powder (YNBY) is a positive control. Add 1 mL of fresh anticoagulated rabbit blood to each of the above tubes to allow the material to fully contact the blood, and use calcium chloride (0.2 M, 50 μL) to start coagulation. Then place the centrifuge tube in a 37 °C water bath, tilt and observe every 15 s until the blood is completely coagulated and stops flowing, and record the coagulation time. Repeat the above experiment 3 times, and the final coagulation time result is expressed as Mean ± SD.
[0072] The in vitro coagulation time experiment confirmed the in vitro procoagulant performance of the material. Figure 8 The in vitro coagulation of 20 mg of different samples and 4 mg of ADP is shown. The coagulation time of the HA-ADP group and the YNBY powder group was shortened by more than 24% compared with the blank group. The in vitro coagulation time of the blank group was (20.94 ± 1.18) min; the in vitro coagulation time of the HA-ADP (1:1) group was (9.96 ± 0.27) min; the in vitro coagulation time of the HA-ADP (2:1) group was (10.91 ± 0.43) min; the in vitro coagulation time of the HA-ADP (3:1) group was (12.78 ± 0.85) min; the in vitro coagulation time of the HA group was (15.78 ± 1.86) min; the in vitro coagulation time of the YNBY group was (13.04 ± 0.18) min. No coagulation state occurred in the ADP group because 20 mg HA-ADP corresponds to about 4 mg of ADP monomer content, and the safe dose of ADP monomer is 1 mg. The content of about 4 mg may cause hemolysis in the blood and damage red blood cells, so no coagulation occurred. Compared with the YNBY group, the HA-ADP (1:1) group could significantly shorten the in vitro coagulation time, indicating that HA-ADP (1:1) has good procoagulant activity in vitro.
[0073] 2. In vitro coagulation index determination Accurately weigh 20 mg of the test sample (HA-ADP and Yunnan Baiyao powder, HA and ADP are converted according to the maximum content of HA-ADP) and place it in a 10 mL centrifuge tube. The blank centrifuge tube is a negative control, and the Yunnan Baiyao powder is a positive control. Store it in a 37°C water bath for preheating. Add 1 mL of fresh anticoagulated whole blood to each of the above tubes to allow the material to fully contact the blood, and use calcium chloride (0.2 M, 30 μL) to initiate coagulation. After 10 min, add 5 mL of deionized water to mix with the above solution and centrifuge. The relative absorbance of the supernatant obtained at 545 nm is marked as a, and the absorbance of the blank anticoagulated whole blood mixture that initiates coagulation is b. Each group has 3 replicate samples. The calculation formula for the coagulation index (BCI) is calculated according to the following formula: Distilled water swells uncoagulated red blood cells to release hemoglobin, and the BCI value is evaluated by the absorbance value of its solution, where a smaller BCI value indicates the rapid coagulation ability of the hemostatic material. Fig. 9 As shown in the figure, the BCI value of fresh anticoagulated whole blood was determined to be 100%, and the BCI values of all samples were lower than that of the blank control, indicating that the prepared samples had good procoagulant properties. Fig. 9 As shown in the figure, the in vitro coagulation of 20 mg of different samples and 4 mg of ADP, the BCI index of the HA-ADP (1:1) group was 1.88%; the BCI index of the HA-ADP (2:1) group was 1.73%; the BCI index of the HA-ADP (3:1) group was 6.76%; the BCI index of the YNBY group was 8.22%; the BCI index of the ADP group was 103.45%, which was consistent with the in vitro coagulation time results. Compared with the YNBY group, there was no statistical difference in the in vitro coagulation effect of HA-ADP. The results show that HA-ADP can promote blood coagulation in vitro.
[0074] 3. Thromboelastography Thromboelastography was measured using a thromboelastometry (TEG) analyzer. Anticoagulated whole blood was mixed with HA-ADP at a ratio of 5 mg / mL. 1 mL of the mixed plasma was added to reagent 1 in the thromboelastometry kit and incubated for 1 min to activate coagulation. The test cup was placed on the thromboelastometry instrument, reagent 2 (CaCl2 reagent) in the kit was added to the test cup, and then 340 μL of whole blood mixed with reagent 1 was added to the test cup to start the test. The negative control group was sodium citrate anticoagulated whole blood without sample. The above experiment was repeated 3 times, and the final results were expressed as Mean ± SD.
[0075] The results of thromboelastography are shown in Table 5. Compared with the blank group, the R values of the HA-ADP group were all reduced, indicating that HA-ADP can shorten the coagulation initiation time, further proving that it can activate the intrinsic and extrinsic pathways of the coagulation cascade reaction; the increase in the α angle indicates that HA-ADP can accelerate the formation and cross-linking of fibrin, and the decrease in the K value indicates that HA-ADP can accelerate the formation of blood clots, further proving that it can activate platelets, accelerate the formation of fibrin network, and facilitate the formation of blood clots. Multiple indicators of thromboelastography can show that HA-ADP can achieve the purpose of rapid coagulation by shortening multiple steps in the coagulation process.
[0076] Table 5 Thromboelastography analysis of HA-ADP 4. Prothrombin time and activated partial thromboplastin time determination The activated partial thromboplastin time (APTT) and prothrombin time (PT) were tested to determine whether the material activated the endogenous or exogenous coagulation pathway. 10 mg HA-ADP was mixed with 2 mL PPP and incubated at 37 °C for 30 min. The upper layer of serum was placed in the RAC-030 fully automatic coagulation analyzer and reacted with APTT and PT reagents, respectively. Each sample was tested 3 times in parallel, and the test results were expressed as Mean ± SD.
[0077] PT and APTT are two important indicators for determining the external and internal coagulation pathways. Fig.10 As shown in the figure, compared with the blank group, the PT results showed that the HA-ADP group could significantly shorten the exogenous coagulation time (***p<0.001); the APTT results showed that the HA-ADP (1:1) group and the HA-ADP (2:1) group could significantly shorten the intrinsic coagulation time. The APTT and PT coagulation times of the HA-ADP (1:1) group were shortened by 12.26% ± 1.87% and 45.08% ± 3.44%, respectively. Based on the above results, it is speculated that HA-ADP can activate the intrinsic and extrinsic pathways of the coagulation cascade reaction.
[0078] 5. Platelet activation experiment 1 mL of the test sample (5 mg / mL HA-ADP) was mixed with 200 μL PRP (10 8 / mL) at 37 ℃ for 10 min, centrifuge at 1200 × g for 10 min and discard the supernatant. Add 200 μL PBS and blow repeatedly to form a platelet suspension. Platelets without sample treatment were used as blank controls. APC-CD62P and PE-CD61 were added and mixed thoroughly. The mixture was incubated at 4 ℃ in the dark for 20 min. 1 mL Cell Staining Buffer was added to wash the unbound antibodies, centrifuge at 350 × g for 5 min and discard the supernatant, repeat the washing 2 to 3 times, and then add 0.5 mL Cell Staining Buffer and mix well before detection by flow cytometer.
[0079] By labeling resting and activated platelets with PE-CD61, activated platelets that can be labeled with APC-CD62P were screened out, thereby obtaining the proportion of platelets activated by HA-ADP. Fig.11 As shown, the results of flow cytometry experiments showed that HA-ADP could significantly activate platelets, and the activation ability was significantly higher than that of raw material ADP, proving that HA-ADP has a good ability to activate platelets.
[0080] 6. Study on the interaction between HA-ADP and FXII factor Freshly collected sodium heparin anticoagulated whole blood was centrifuged at 1000 × g for 15 min, and the supernatant was taken for later use. 5 mg HA-ADP was mixed with 1 mL plasma and incubated for 30 min. Platelets without sample treatment were used as blank controls. The blank group samples were diluted 15 times, and the experimental group samples were diluted 10 times. The FXII factor content in the supernatant was determined according to the instructions of the rat coagulation factor XII enzyme-linked immunosorbent assay kit, and the changes in the FXII factor in the plasma before and after the addition of HA-ADP were calculated according to the established FXII concentration-OD value standard curve. The standard curve is shown in Fig.12 (a) shown.
[0081] like Fig.12 As shown in (b), the results of the HA-ADP and FXII interaction experiment showed that the FXII content in blank plasma was 43.28 ng / mL; the FXII content in the HA-ADP (1:1) group was 32.88 ng / mL; the FXII content in the HA-ADP (2:1) group was 37.95 ng / mL; and the FXII content in the HA-ADP (3:1) group was 38.92 ng / mL, indicating that the negative charge on the surface of HA-ADP can promote the conversion of FXII in the intrinsic coagulation pathway to FXIIa, thereby accelerating the activation of the coagulation pathway.
[0082] In this embodiment, the results of the in vitro coagulation experiment show that HA-ADP (1:1) has the best in vitro coagulation effect, which may be due to the fact that the ability of ADP to activate platelets to promote hemostasis is higher than its own electronegativity to shorten the coagulation time to promote hemostasis. Studies on the hemostatic mechanism have shown that HA-ADP can achieve hemostasis through multiple effects such as activating platelets, activating intrinsic and exogenous coagulation pathways, and accelerating the formation and cross-linking of fibrin.
[0083] Example 4 Study on the biocompatibility and in vivo hemostatic properties of a fully degradable hyaluronic acid composite material (HA-ADP) 1. In vitro hemolysis test The effect of HA-ADP on in vitro hemolytic performance was evaluated using rat whole blood. Fresh rat whole blood was mixed with 3.8% sodium citrate in a ratio of 9:1, and then fresh anticoagulated whole blood was diluted with normal saline in a ratio of 1:1 for later use. 10 mg of HA-ADP of three formulations, 10 mg of control group HA, and 4 mg of ADP samples were weighed and placed in 10 mL centrifuge tubes, and 200 μL of anticoagulated whole blood and 5 mL of normal saline were added to the diluted anticoagulated whole blood. The determination method and result judgment were the same as the in vitro hemolytic experiment in Example 1.
[0084] Since hemostatic materials are in direct contact with blood, inducing no or minimal hemolytic activity is a necessary prerequisite for hemostatic materials. Fig.13 As shown in the figure, the amount of ADP contained in the 10 mg HA-ADP sample has a certain hemolysis rate (9.20% ± 0.99%), and the hemolysis rates of HA and all prepared samples are lower than 5% (the maximum level of acceptable blood compatibility), indicating that the hemolytic activity of the prepared samples is not significant and the hemolysis of ADP is improved. Among them, the hemolysis rate of HA-ADP (1:1) is the lowest (0.46% ± 0.39%). The above results show that HA-ADP has good blood compatibility.
[0085] 2. In vitro cytotoxicity assay In this experiment, the MTT assay and Calcein-AM / PI live / dead cell double staining kit were used to detect the cell compatibility of HA-ADP. HA-ADP was prepared into a 2 mg / mL solution using complete culture medium as solvent for later use.
[0086] MTT assay: Mouse fibroblasts (L929) were inoculated into 96-well plates at a density of 1500 cells per well. After 24 h of cell culture, the original culture medium was discarded, and 100 μL of HA-ADP solution was added to each well. The cells were co-cultured with L929 cells for 24 h, 48 h, and 72 h, respectively. The DMEM complete culture medium group was used as the blank group. After that, the liquid in each well was discarded, and 50 μL of freshly prepared 1 mg / mL MTT solution was added to each well, and the cells were placed in the incubator for another 2 h. After 2 h, the liquid in each well was discarded, and 100 μL of isopropanol solution was added to each well. The crystal violet precipitate was fully dissolved by vortexing for 10 min. The absorbance value of each well was measured at 570 nm and 650 nm (calibration wavelength) on a microplate reader, and the relative proliferation rate (Relative Growth Rate, RGR) of the cells was calculated according to the following formula. Six parallel wells were set for each sample: Calcein-AM / PI live / dead cell double staining kit detection method: L929 was inoculated into a 12-well plate at a density of 10,000 cells per well. After 24 h of cell culture, the original culture medium was discarded, and 500 μL HA-ADP solution was added to each well and co-cultured with L929 cells for 24 h, 48 h, and 72 h, respectively. The DMEM complete culture medium group was used as the blank group. According to the instructions of the Calcein-AM / PI live / dead cell double staining kit, Calcein-AM and PI were used to double-stain live and dead cells at the same time. The levels of live and dead cells were analyzed using an inverted fluorescence microscope. Each sample had 3 replicate wells.
[0087] Biocompatibility is a necessary requirement for hemostatic materials that can promote wound healing. Therefore, we used L929 cells as a model to study the effects of samples on cells using MTT and live / dead staining assays. Fig.14 As shown in the figure, after co-culture with the DMEM solution of HA-ADP samples for 24, 48, and 72 hours, the cell proliferation rate of the 2 mg / mL concentration sample was similar to that of the control group, and the cell viability was greater than 75%. Among them, the cell proliferation rate of the HA-ADP (1:1) group was the highest. In addition, the direct contact between cells and samples was also confirmed by using a live / dead staining test. Fig.15 As shown, the results of each group of cells showed good proliferation, the fluorescence of the cells was mostly green, and the morphology was normal. These results show that HA-ADP can promote cell proliferation and thus support wound healing after hemostasis.
[0088] 3. Systemic acute toxicity test HA-ADP was prepared into 7.5, 5, 2.5, and 1 mg / mL aqueous solutions with distilled water as the solute. Twenty-five healthy Kunming mice were randomly divided into five groups. The experimental group animals were given 20 mL / kg HA-ADP solution by oral gavage once, and the control group animals were given distilled water in the same way. After administration, the immediate reaction of all mice and the systemic toxicity manifestations of 4 h and 1 to 7 days were observed and recorded. The mice were weighed every day before the start of the experiment and at the end of the experiment. During the experiment, if the biological reaction of the animals injected with HA-ADP solution was no greater than that of the animals in the saline group, HA-ADP met the safety requirements. If 2 or more animals in the HA-ADP group died, or convulsed, or lay prone; if 3 or more animals lost more than 10% of their initial body weight, HA-ADP was judged to have systemic acute toxicity.
[0089] After 7 consecutive days of observation, the KM mice were generally in good condition, with no deaths, convulsions or proneness. In the first 4 hours after oral administration, the activity of the mice decreased, and then quickly returned to normal. This phenomenon occurred because a large amount of liquid was given at one time, and the state recovered quickly after the liquid was absorbed. Fig.16 As shown, it can be seen that the weight changes of mice in the sample groups with different concentrations are consistent with those in the distilled water group, and have been showing a steady growth. The experimental results show that HA-ADP does not cause acute toxic reactions.
[0090] 4. Mouse liver injury and bleeding model Twelve healthy Balb / c mice weighing 19 to 21 g were randomly divided into two groups according to body weight. The mice were anesthetized by intraperitoneal injection of 0.2 mL of a mixed solution of ketamine hydrochloride injection and xylazine. The limbs of the mice were fixed to the surgical board, and the abdomen was depilated and disinfected. A 1 cm opening was made along the upper abdomen to expose the left lobe of the liver. A puncture needle was used to establish a bleeding site with a length of 0.8 cm and a depth of 2 mm. Free bleeding was allowed for 5 s, and then hemostasis was performed. The experimental group used 10 mg HA-ADP (1:1) sample. The blank group did not receive any treatment. The total amount of bleeding was collected using sterile filter paper, and the hemostasis time was recorded. Hemostasis was considered successful when there was no more blood flow on the surface of the vertically placed filter paper. After hemostasis, the mice in the blank group were euthanized, and the mice in the experimental group had their wounds sutured. The degradation of HA-ADP in the body was observed, and the weight changes of the mice were recorded. The injured part was cut off and fixed in formalin solution (40% formaldehyde solution diluted 10 times) for 1 week to observe whether the liver tissue had pathological changes. Fig.17 .
[0091] The hemostatic efficacy based on the mouse liver injury bleeding model is shown in Fig.18The hemostatic properties of HA-ADP (1:1) in vivo were evaluated in a mouse liver injury bleeding model, with hemostatic time and blood loss as evaluation indicators of hemostatic activity. Fig.18 As shown in (a), the blood loss in the HA-ADP group was (5.87 ± 2.63) mg; the blood loss in the blank group was (21.40 ± 13.22) mg. Compared with the blank group, the blood loss in the HA-ADP group was reduced by about 72.43%, significantly reducing the amount of liver injury and bleeding in mice (*p<0.05). Fig.18 As shown in (b), the hemostasis time of the blank group was (2.71 ± 0.44) min; the hemostasis time of the HA-ADP group was (1.05 ± 0.43) min. Compared with the blank group, the HA-ADP group can shorten the hemostasis time by 60.89%, which has a significant hemostatic advantage (***p<0.001). In summary, HA-ADP can reduce blood loss and shorten hemostasis time in the mouse liver injury bleeding model, indicating that HA-ADP has a good hemostatic effect.
[0092] The safety and degradation time of HA-ADP (1:1) in vivo were observed by suturing mice that had been hemostatically treated with HA-ADP (1:1). Balb / c mice were euthanized to observe the degradation of HA-ADP (1:1) in vivo. Fig.19 (a) On the second day after surgery, HA-ADP (1:1) was attached to the left lobe of the liver in a flocculent state. On the fifth day after surgery, HA-ADP (1:1) was completely degraded. Balb / c mice were observed for 7 consecutive days after surgery. There was no death, convulsion or prone position. The weight changes were as follows: Fig.19 As shown in (b), it can be seen that the weight of the mice has been gradually increasing; the histological analysis of the liver after hemostasis is shown in Fig.19 As shown in (c), no inflammation, necrosis, hemorrhage, or pathological changes such as hepatic sinusoidal dilation were observed in the tissue, indicating that HA-ADP (1:1) has good safety in vivo.
[0093] In this example, the in vitro and in vivo biocompatibility and hemostatic activity of HA-ADP in living animals were evaluated by in vitro cytotoxicity, in vitro hemolysis, systemic acute toxicity and mouse liver injury bleeding model experiments. The experimental results are as follows: (1) Biocompatibility: Analysis of the results of in vitro hemolysis and in vitro cytotoxicity experiments showed that HA-ADP (1:1), HA-ADP (2:1), and HA-ADP (3:1) in three ratios can be used. The results of in vitro hemolysis, in vitro cytotoxicity, and systemic acute toxicity experiments showed that HA-ADP (1:1) has the best blood compatibility, cell compatibility, and no systemic acute toxicity among the three reaction ratios. Among them, the hemolysis rate of 10 mg HA-ADP (1:1) is 0.46%, but the hemolysis rate of the 4 mg ADP monomer it contains is 9.20%, which has the disadvantage of poor blood solubility; the cell proliferation rate of the 2 mg / mL HA-ADP (1:1) group is the highest; the weight of mice in the 7.5 mg / mL HA-ADP (1:1) group has the same growth trend as the normal saline group.
[0094] (2) Hemostatic effect: In the mouse liver injury bleeding model, compared with the blank group, HA-ADP (1:1) can significantly shorten the hemostatic time by 61.3% and significantly reduce the blood loss by 72.6%. It is completely degraded in the body within 5 days, and the weight of the mice increases steadily.
[0095] In summary, the hemolytic properties of ADP were improved with the addition of HA; local application of HA-ADP did not induce hemolysis or thrombosis in mice, indicating that HA-ADP has good hemostatic activity, safety and complete in vivo degradability.
Claims
1. A degradable composite hyaluronic acid polymer hemostatic material, characterized in that: The hyaluronic acid and adenosine diphosphate are used as raw materials, and a condensing agent and an activating agent are added to undergo an amidation reaction to prepare the hyaluronic acid. The molar ratio of the hyaluronic acid, adenosine diphosphate, the condensing agent and the activating agent is (1-3):1:1:
1.
2. The degradable composite hyaluronic acid polymer hemostatic material according to claim 1, characterized in that: The condensing agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, and the activating agent is 1-hydroxybenzotriazole.
3. The method for preparing the degradable composite hyaluronic acid polymer hemostatic material according to claim 1 or 2, characterized in that: The method comprises the following steps: dissolving hyaluronic acid in deionized water, adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole, dissolving, adding adenosine diphosphate, purifying after the reaction, so as to obtain a hemostatic material HA-ADP, and storing after drying, wherein the molar ratio of the hyaluronic acid, adenosine diphosphate, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole is (1-3):1:1:
1.
4. The preparation method according to claim 3, characterized in that: The molar ratio of the hyaluronic acid, adenosine diphosphate, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1-hydroxybenzotriazole is 1:1:1:
1.
5. The preparation method according to claim 3, characterized in that: When dissolving hyaluronic acid in deionized water, the ratio of hyaluronic acid to deionized water is: 100-150 mL of deionized water per 1 g of hyaluronic acid; Preferably, the ratio of the hyaluronic acid to deionized water is: 100 mL of deionized water per 1 g of hyaluronic acid.
6. The preparation method according to claim 3, characterized in that: The reaction is carried out under stirring for at least 24 hours.
7. The preparation method according to claim 3, characterized in that: The purification is performed by dialysis, the molecular weight cut-off of the dialysis is 3500 Da, the dialysis time is 96 hours, the dialysate of the dialysis is deionized water, and the deionized water is replaced every 12 hours.
8. The preparation method according to claim 3, characterized in that: The drying is carried out by freeze drying.
9. The degradable composite hyaluronic acid polymer hemostatic material prepared by the preparation method according to any one of claims 3 to 8.
10. Use of the degradable composite hyaluronic acid polymer hemostatic material according to claim 1, 2 or 9 in the preparation of medical hemostatic products.
Citation Information
Patent Citations
Hemostatic material with antibacterial and anti-inflammatory functions as well as preparation method and application thereof
CN114832148A
Hyaluronic acid-based hydrogel precursor solution, hyaluronic acid-based hydrogel as well as preparation method and application of hyaluronic acid-based hydrogel
CN117567744A
Preparation method of hyaluronic acid microbeads and use of hyaluronic acid microbeads
WO2019221432A1
High-efficiency hemostatic material, and preparation method therefor and use thereof
WO2024217056A1